(untitled) - Bagaric, Mirko (South Yarra, Vic., 2011)
Explains, analyses and evaluates the principles of torts law. It also explores a rational for torts law reform. Authors from Deakin University, Australia.
Keywords: Vi phạm pháp luật,Torts; Úc,Australia